Pelatihan self compassion untuk mengurangi perilaku bullying siswa SD di Kota Makassar - Widyastuti Widyastuti; Ahmad Rifdah (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
Bullying is an abnormal, unhealthy, and socially unacceptable behavior in the social environment. The number of bullying cases that occurred lately has been triggered by various kinds of things such as lack of knowledge about bullying or a less strict school rules system and trivial assumptions about bullying treatment. If the society ignored this issue, it will have a very fatal impact because it will unconsciously provide bullies power to the bullying actors, create unhealthy social interaction, and increase the culture of violence. Therefore the need to develop a sense of empathy, respect and love among students is crucially needed by providing compassion training so that bullying behavior can be minimized.